A Review Of Road‒Related Soil Erosion: An Assessment Of Causes, Evaluation Techniques And Available Control Measures - Khoboso Elizabeth Seutloali; Heinrich Reinhard Beckedahl (Earth Sciences Research Journal)
Road construction has increased significantly worldwide in the last decades to meet the demands of the increasing human population and this has led to serious soil erosion problems, the bulk of which is unaccounted for, especially in the developing world. For comprehensive land management decisions and monitoring strategies, a review of work that has been done to assess soil erosion due to roads is critical. This article, therefore, reviews the causes of road‒related soil erosion, assessment methods and available control measures. Specifically, work provides an overview of (i) the linkages between roads and soil erosion; (ii) measurement and prediction of road‒related erosion; and (iii) erosion control and rehabilitation techniques. Literature shows that road construction results in hill-slope profile modification; removal of vegetation cover; as well as the formation of steep slopes that are prone to severe erosion. Furthermore, there is a variety of erosion control measures for controlling road‒related erosion although no study has demonstrated the method that is cost efficient and operational across different landscapes. We are of the view that this study provides guidance in future research on road‒related soil erosion across the developing world were sophisticated monitoring techniques are limited due to resource scarcity for assessing large areas.